Bentonite as a Functional Material Enhancing Phytostabilization of Post-Industrial Contaminated Soils with Heavy Metals - Klik, Barbara; Holatko, Jiri; Jaskulska, Iwona; Gusiatin, Mariusz Z; Hammerschmiedt, Tereza; Brtnicky, Martin; Liniauskienė, Ernesta; Baltazar, Tivadar; Jaskulski, Dariusz; Kintl, Antonin; Radziemska, Maja (Materials (Basel, Switzerland), 2022)
Growing awareness of the risks posed by pollution of the soil environment is leading to the development of new remediation strategies. The technique of aided phytostabilization, which involves the evaluation of new heavy-metal (HM)-immobilizing amendments, together with appropriately selected plant species, is a challenge for environmental protection and remediation of the soil environment, and seems to be promising. In this study, the suitability of bentonite for the technique of aided phytostabilization of soils contaminated with high HM concentrations was determined, using a mixture of two grass species. The HM contents in the tested plants and in the soil were determined by flame atomic absorption spectrometry. The application of bentonite had a positive effect on the biomass of the tested plants, and resulted in an increase in soil pH. The concentrations of copper, nickel, cadmium, lead and chromium were higher in the roots than in the above-ground parts of the plants, especially when bentonite was applied to the soil. The addition of the analyzed soil additive contributed significantly to a decrease in the levels of zinc, copper, cadmium and nickel in the soil at the end of the experiment. In view of the above, it can be concluded that the use of bentonite in the aided phytostabilization of soils polluted with HMs, is appropriate.
Keywords: amendments; metal immobilization; risk minimization; soil contamination